Procedural Semantics for Hyperintensional Logic - Duží, Marie. author. aut Link
XIII, 550 p.
Keywords: July 2011 -- The Council of the Academy of Sciences of the Czech Republic has presented Procedural Semantics for Hyperintensional Logic with its prestigious award for outstanding results of major scientific importance. This volume sets out the foundations of Transparent Intensional Logic, together with many applications to a wide range of topics including formal semantics, philosophy of language, and philosophical logic. Special attention is devoted to some topics that generally tend to be dealt with only in passing. They include, inter alia, notional attitudes, knowing whether, concepts (understood rigorously and non-mentalistically), attitudes de re, and anaphora in hyperintensional contexts. The overall programme is set out and placed in historical and systematic context. The programme consists in devising one overarching semantic theory for all sorts of discourse, whether colloquial, scientific, mathematical or logical. The semantic theory is a procedural one, according to which sense is an abstract, pre-linguistic procedure detailing what operations to apply to what procedural constituents to arrive at the product (if any) of the procedure. Such procedures are rigorously defined as so-called constructions residing in a platonic realm. The semantics is tailored to the hardest case, as constituted by hyperintensional contexts, and generalized from there to intensional and extensional contexts. This anti-contextualist and fully compositional semantics is, to the best of our knowledge, the only one that deals with all kinds of context in a unique and systematic manner. The three authors have striven to write an accessible study of Transparent Intensional Logic that may be read by researchers and advanced students of logic, semantics, linguistics, informatics, computer science, and kindred disciplines.